I need some help solving the following:

a) (2)*3^x = (7)*5^x

b) 12^x = (4)*8^(2x)

c)(12)*6^(2x-1) = 11^(x+3)

d) (7)*0.43^(2x) = (9)*6^(-x)

Thanks.

Printable View

- May 22nd 2008, 07:20 PMandymacLogarithms!
I need some help solving the following:

a) (2)*3^x = (7)*5^x

b) 12^x = (4)*8^(2x)

c)(12)*6^(2x-1) = 11^(x+3)

d) (7)*0.43^(2x) = (9)*6^(-x)

Thanks. - May 22nd 2008, 07:28 PMMathstud28
Two methods for these. I will show you both for the first problem and you can apply it to the rest

**Method one**

taking the natural log of both sides gives

Algebraically manipulating gives

so

**Method two**

through manipulation we get

taking the natural log of both sides gives